Recipient sex and donor leukemic cell characteristics determine leukemogenesis in patient-derived models - Anna MP. Stanger; Marlon Arnone; Pauline Hanns; Lucca M. Kimmich; Jessica Kübler; Sarah Gekeler; Elsa S. Görsch; Lea Kramer; Marcelle Baer; Jan C. Schroeder; Taylor S. Mills; Martina Konantz; et al. (Haematologica)
In acute myeloid leukemia (AML), leukemogenesis depends on cell-intrinsic genetic aberrations and thus, studies on AML require investigations in an in vivo setting as provided by patient derived xenografts (PDX) models. Here we report that, next to leukemic cell characteristics, recipient sex highly influences the outgrowth of AML cells in PDX models, with females being much better repopulated than males in primary as well as secondary transplantation assays. Testosterone may be the more important player since, strikingly, better engraftment was seen in castrated versus control male recipients, while ovariectomy did not significantly impair engraftment in females. Shorter time-to-engraftment and mouse survival were observed with adverse molecular risk, and respectively with high FLT3-ITD ratio mutated AML cells. Adverse risk AML furthermore showed higher percentages of phenotypic leukemic stem cells (LSCs), suggesting impaired differentiation capacity in these AML subtypes. Overall, we achieved successful repopulation with 14/23 (61%) favorable, 18/30 (60%) intermediate and 4/8 (50%) adverse risk AML cases in female recipient PDX models. Our data identify recipient sex as an important experimental confounder in leukemia PDX models, and the contribution of the sex hormones to leukemogenesis as an intriguing, underexplored research area.